Decidual dendritic cells 10 and CD4+CD25+FOXP3 regulatory T cell in preeclampsia and their correlation with nutritional factors in pathomechanism of immune rejection in pregnancy. (December 2022) - Silalahi, Eva Roria; Wibowo, Noroyono; Prasmusinto, Damar; Djuwita, Ratna; Rengganis, Iris; Mose, Johanes C.
Abstract: Background: Immune intolerance is thought to be the underlying cause of immune rejection to fetus in preeclampsia. Decidual dendritic cell-10 (DC-10) and T regulator cell (Treg) play important role to create tolerogenic environment during pregnancy. However, their roles on the specific pathomechanism of preeclampsia along with various nutritional factors have not been widely studied. Aim: To determine the number of DC-10 and Treg in preeclampsia and their correlations with decidual nutritional factors. Method: This was a cross-sectional study among early onset preeclampsia (EOPE), late onset preeclampsia (LOPE), and normotensive (NT) pregnancies. Decidual specimens were obtained by curettage after caesarean section. The number of DC-10 and Treg cells were counted using flow cytometry. The levels of nutritional factors (zinc, retinol, all-trans retinoic acid, vitamin D) were determined using ICP-MS and LC-MS method. Result: A total of 14 subjects for each group were included in the study. The DC-10 was significantly lower in both EOPE and LOPE compared to NT (p < 0.001). Treg cells were significantly higher in EOPE compare to NT (p = 0.015). There was a moderate correlation between zinc level and DC-10 (p = 0.011) and a strong correlation between retinol level and DC-10 (p = 0.002) in the NT group. A moderate correlation was found between vitamin D level and Treg cells in the NT group (p = 0.026). Conclusion: There was a lower number of DC-10 and higher number of Treg cells in early preeclampsia. There was no correlation between DC-10 and Treg number with decidual nutritional factors in preeclampsia. Highlights: Immune intolerance during placentation plays a significant role in the pathomechanism of preeclampsia. Chronic inflammatory response on pregnancy with preeclampsia has created significant changes since decidualization. There are no correlation between various nutritional factors and tolerogenic factors in pregnancy with preeclampsia.